2006
DOI: 10.1080/13803610500392053
|View full text |Cite
|
Sign up to set email alerts
|

Californian science students' perceptions of their classroom learning environments

Abstract: This study utilised the What Is Happening In this Class (WIHIC) questionnaire to examine factors that influence Californian students' perceptions of their learning environment. Data were collected from 665 USA middle school science students in 11 Californian schools. Several background variables, such as gender, socioeconomic status, ethnicity, and class size, were included in the study. A hierarchical analysis of variance was conducted. Results from this study indicate that some scales of the WIHIC are more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 13 publications
2
20
0
2
Order By: Relevance
“…It has been shown that enjoyment (or pleasure) is strongly related to other attitudinal concepts and elements, such as relevance, confidence, interest and effort (e.g. den Brok 2001). Thus, the more enjoyment that students experience in science, the more relevance that they attach to science for their future education and occupation, the more confidence that they have in performing well in science, the more interested that they are in science, and the more effort that they are willing to invest into learning science.…”
Section: Students' Science-related Attitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that enjoyment (or pleasure) is strongly related to other attitudinal concepts and elements, such as relevance, confidence, interest and effort (e.g. den Brok 2001). Thus, the more enjoyment that students experience in science, the more relevance that they attach to science for their future education and occupation, the more confidence that they have in performing well in science, the more interested that they are in science, and the more effort that they are willing to invest into learning science.…”
Section: Students' Science-related Attitudesmentioning
confidence: 99%
“…The Australian version of the QTI has shown adequate reliability and validity, both for primary and secondary education students (e.g. den Brok 2001;Fraser 2002;Wubbels and Levy 1993).…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations